Quantitative Research and Characterization of the Loess Microstructure in the Bai Lu Tableland, Shaanxi Province, China - Longsheng Deng; Wen Fan; Shaopeng Liu; Yupeng Chang; Yan Dai; Yubo Li (Advances in Civil Engineering)
Loess is a special geotechnical material with strong structural properties, and the microstructural characteristics of loess significantly influence its macroscopic physical features, mechanical properties, and catastrophic behavior. In this paper, serial samples were extracted from the continuous loess and paleosol strata of the Bai Lu tableland; with these samples, the optical microscopy-based serial sectioning method was adopted to study the quantitative characterization and variation in the loess microstructure. Three-dimensional characteristics and quantitative parameters of the particles, pores, and throats of the loess were obtained. The results indicate that the volume, Eq-Radius, and major-minor axis ratio of the loess particles satisfy third-order, third-order, and second-order Gaussian distributions, respectively. The Eq-Radius of the loess pores and throats satisfies a first-order Gaussian distribution, and the throat channel length satisfies a gamma distribution. With increasing stratum depth, the particles become more flattened, the throat radii become larger and the pore channels become slenderer. The variation in fitting parameters and the correlations between the macrophysical and mechanical properties of loess were then explored. The study of the microstructure of loess contributes to a better understanding of the catastrophic behavior of loess and the physical mechanism of geologic hazards in this area.